Research progress on environmental stability of SARS-CoV-2 and influenza viruses - Zhang, Ling; Fang, Zhongbiao; Li, Jiaxuan; Huang, Zhiwei; Tie, Xiaotian; Li, Hongyu; Li, Jianhua; Zhang, Yanjun; Zhang, Yuanyuan; Chen, Keda (Frontiers in Microbiology, 2024)
We reviewed research on SARS-CoV-2 and influenza virus detection on surfaces, their persistence under various conditions, and response to disinfectants. Viral contamination in community and healthcare settings was analyzed, emphasizing survival on surfaces influenced by temperature, pH, and material. Findings showed higher concentrations enhance survivability at room temperature, whereas stability increases at 4°C. Both viruses decline in low pH and high heat, with influenza affected by salinity. On various material surfaces, SARS-CoV-2 and influenza viruses demonstrate considerable variations in survival durations, and SARS-CoV-2 is more stable than influenza virus. On the skin, both virus types can persist for ≥2 h. Next, we delineated the virucidal efficacy of disinfectants against SARS-CoV-2 and influenza viruses. In daily life, exposure to ethanol (70%), isopropanol (70%), bleach (10%), or hydrogen peroxide (1–3%) for 15–30 min can effectively inactive various SARS-CoV-2 variants. Povidone-iodine (1 mg/mL, 1 min) or cetylpyridinium chloride (0.1 mg/mL, 2 min) may be used to inactive different SARS-CoV-2 variants in the mouth. Chlorine disinfectants (500 mg/L) or ultraviolet light (222 nm) can effectively inhibit different SARS-CoV-2 variants in public spaces. In conclusion, our study provides a scientific basis and practical guidance for reduction of viral persistence (retention of infectivity) on surfaces and environmental cleanliness.